Camisea, compensation and diversification of livelihoods in the native community of Cashiriari (Cusco- Perú) - del Castillo Tafur, Cynthia (2015)
The Camisea Gas Project, which is one of the largest gas exploration and exploitation projects in Latin America, has been operating since 2000 in the southeast Amazon of Cusco in Peru, in territory historically occupied by Machiguenga indigenous populations. The Machiguenga Native Community of Cashiriari, where my fieldwork is based, undergoes huge processes of social transformation, among other reasons, due to the money received as compensation from the Camisea Consortium for the environmental impacts in their territory, and to the indigenous labour policy, which involves hiring Machiguenga men to work as wage-labourers at the Camisea gas fields. The subsistence economy (through hunting, fishing, gathering, agriculture) has become insufficient, and making money has become a need in the community; the traditional division of labour has shifted because of women and men’s (migrant) wage labour, increasing women’s household burden; diversification of livelihood activities has become a feature of Machiguenga households, in particular among women. Finally, there is a generalized perception among the community of material development but of decline in natural resources and cultural traditions.